Existence and Stability Results for Thermodiffusion Laminated Beam System with Delay Feedback - Zineb Khalili; Djamel Ouchenane; Ali Krelifa; Imene Laribi; Salah Boulaaras; Ahmed Himadan Ahmed (Mathematics)
In this paper, a one-dimensional thermodiffusion laminated beam system with delay feedback is studied. The existence of a solution for our system is discussed within the context of the semigroup approach. In addition, under different boundary conditions, two results of stability properties independent of initial data are investigated.